Evaluasi Kerjasama dalam Pengembangan Perpustakaan Universitas Riau dengan Perpustakaan Arsip dan Dokumentasi Provinsi Riau - Yulia, Fera; ., Rismayeti; Amelia, Vita (Pustaka : Jurnal Ilmu-Ilmu Budaya; Vol 22 No 1 (2022), 2022)
This research is entitled "Evaluation of Cooperation in the Development of the Riau University Library with the Archives and Documentation Library of Riau Province". The purpose of this research is to find out the form of realization of cooperation and what are the obstacles faced by the Riau University Library with the Riau Province Archives and Documentation Library in the development of the Riau University library. The method used in this research is qualitative method. Data collection techniques using interviews. With the number of informants as many as 10 people. The results of data analysis show that the form of realization of collaboration with the Riau University library is collaborating with the Archives and Documentation Library of Riau Province, namely. Becoming a Member of the Suman HS Regional Library With the Electronic system, the collaboration has not been implemented. The obstacles faced by the Riau University Library and the Riau Province Documentation Archives Library are the change in the head of the library, lack of coordination between leaders, the application is not integrated, and the lack of experts on duty.